Sejarah institusi: Perlembagaan dan perkembangan teknologi penginderaan jauh di Indonesia Era Orde Baru - Prabowo, Ra'afian (Historiography: Journal of Indonesian History and Education, 2024)
Abstract The institution for developing remote sensing technology in Indonesia was formed in 1969 during the Soeharto or New Order era and introduced this technology in 1971. The development into an institution was based on several things such as the transformation of science, the institutionalization of remote sensing science, and various political reasons in Soekarno's reign. This article uses a narrative history method and focuses on studying institutional history with the concept of institutionalization. Departing from this research, the author explains several findings presented in this article such as survey and mapping institutions from the Dutch East Indies to the era of the Soekarno government, the establishment of remote sensing technology development institutions in the Soeharto era or the New Order as well as several founding and supporting figures for one of the institutions developer of remote sensing technology.Abstrak Lembaga pengembang teknologi penginderaan jauh di Indonesia telah terbentuk pada tahun 1969 sejak masa Pemerintahan Soeharto atau Orde Baru dan memperkenalkan teknologi tersebut pada tahun 1971. Pengembangan menjadi sebuah institusi didasarkan atas beberapa hal seperti adanya transformasi ilmu pengetahuan, institusionalisasi ilmu penginderaan jauh dan berbagai alasan politis pada masa Pemerintahan Soekarno. Artikel ini menggunakan metode sejarah naratif dan memfokuskan pada kajian Sejarah Institusi dengan konsep perlembagaan. Berangkat dari penelitian ini, penulis memaparkan beberapa temuan yang dipaparkan dalam artikel ini seperti Institusi survei dan pemetaan sejak Hindia Belanda sampai era Pemerintahan Soekarno, pendirian institusi pengembang teknologi penginderaan jauh di Era Pemerintahan Soeharto atau Orde Baru serta beberapa tokoh pendiri dan pendukung untuk salah satu lembaga pengembang teknologi penginderaan jauh tersebut.